Carbon sequestration in riparian forests: A global synthesis and meta‐analysis. (8th November 2018) - Dybala, Kristen E.; Matzek, Virginia; Gardali, Thomas; Seavy, Nathaniel E.
Abstract: Restoration of deforested and degraded landscapes is a globally recognized strategy to sequester carbon, improve ecological integrity, conserve biodiversity, and provide additional benefits to human health and well‐being. Investment in riparian forest restoration has received relatively little attention, in part due to their relatively small spatial extent. Yet, riparian forest restoration may be a particularly valuable strategy because riparian forests have the potential for rapid carbon sequestration, are hotspots of biodiversity, and provide numerous valuable ecosystem services. To inform this strategy, we conducted a global synthesis and meta‐analysis to identify general patterns of carbon stock accumulation in riparian forests. We compiled riparian biomass and soil carbon stock data from 117 publications, reports, and unpublished data sets. We then modeled the change in carbon stock as a function of vegetation age, considering effects of climate and whether or not the riparian forest had been actively planted. On average, our models predicted that the establishment of riparian forest will more than triple the baseline, unforested soil carbon stock, and that riparian forests hold on average 68–158 Mg C/ha in biomass at maturity, with the highest values in relatively warm and wet climates. We also found that actively planting riparian forest substantially jump‐starts the biomass carbon accumulation, with initial growth rates more than double those of naturally regenerating riparian forest. Our results demonstrate that carbon sequestration should be considered a strong co‐benefit of riparian restoration, and that increasing the pace and scale of riparian forest restoration may be a valuable investment providing both immediate carbon sequestration value and long‐term ecosystem service returns. Abstract : We analyzed data from around the world to identify general patterns of carbon sequestration in riparian forests. We found that the carbon stored in mature riparian forest rivals the highest estimates for any biome, and that carbon accumulation is faster over the first ten years in planted forests than naturally regenerating forests. Riparian forests are known to provide multiple ecosystem services, and our results demonstrate that carbon sequestration can be an additional co‐benefit. Despite their relatively small area, investing in riparian forest restoration can be a valuable strategy for contributing to both climate change mitigation and ecological integrity.